Implementasi Sistem Pendukung Keputusan Pemilihan Produk Terlaris Dengan Metode Simple Additive Weighting (SAW) Berbasis Web (Studi Kasus : Dapur Mama El) - Aditiya; Surtikanti (CV. Multi Kreasi Media, 2024)
The large number of food choices makes consumers have the freedom to choose the desired food. To make it easier for potential consumers to choose food products, it is necessary to have a system and application that can help make decisions to determine the desires of potential consumers in the product. Decision Support System (DSS) is a computer-based information system combining models and data to provide support to decision makers in solving semi-structured problems or dependency problems that involve users in depth. Therefore, the problem that has been explained by the author will provide a solution to the product information system design program using the web-based Simple Additive Weighting (SAW) method. The basic concept of the SAW method is to find a weighted sum with a performance rating on each alternative on all attributes, The results show that this best-selling product selection system can help potential consumers to get food alternatives that can be recommended based on criteria that users can choose in choosing foods with the Simple Additive Weighting (SAW) method.